1993
DOI: 10.3109/00365549309008522
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Cytomegalovirus in Bronchoalveolar Lavage by Polymerase Chain Reaction, in Comparison with Virus Isolation and Detection of Viral Antigen

Abstract: Bronchoalveolar lavage (BAL) products from 52 immunocompromised patients with symptoms of pulmonary infection was examined for cytomegalovirus (CMV) by virus isolation, polymerase chain reaction (PCR) and detection of CMV antigen by immunofluorescence or immunoperoxidase staining after short-term incubation in tissue culture and directly in BAL cells. We found that PCR detected all cases positive by virus isolation (15/52 samples) and the result was obtained within 5 h. PCR detected more cases of CMV than did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…These patients showed no signs of CMV pneumonitis and developed no pneumonitis within 1 month, indicating its high negative predictive value for detecting CMV infections in the lung. Our data support similar findings by Eriksson et al [6]. The value of PCR in diagnosis is obvious considering our patient who died of CMV pneumonitis: no other diagnostic tool was successful in detecting CMV, except for PCR of CMV DNA in BAL cells.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These patients showed no signs of CMV pneumonitis and developed no pneumonitis within 1 month, indicating its high negative predictive value for detecting CMV infections in the lung. Our data support similar findings by Eriksson et al [6]. The value of PCR in diagnosis is obvious considering our patient who died of CMV pneumonitis: no other diagnostic tool was successful in detecting CMV, except for PCR of CMV DNA in BAL cells.…”
Section: Discussionsupporting
confidence: 91%
“…Other investigators found this method valuable because of its high specificity of 100%. However, sensitivity in that study was only 26.7% [6]. Therefore, other complementary investigations are necessary to increase the overall sensitivity.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…BAL PCR for CMV was positive in 11 out of 22 episodes but only one case actually had CMV disease. This high positivity for CMV PCR in BAL was also obtained by Eriksson et al [29], who suggested that a positive CMV PCR in BAL cannot always be related to CMV disease and should be correlated with other clinical evidence of CMV disease. They suggested that a combination of PCR and detection of CMV antigen directly in alveolar cells is optimal for rapid and accurate identification of true CMV disease.…”
Section: Discussionsupporting
confidence: 76%